2017
DOI: 10.1292/jvms.17-0294
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of CTX-M-25-producing Enterobacteriaceae in day-old broiler chicks in Japan

Abstract: Day-old chicks from 3 hatcheries were placed on bedding paper and brought to a commercial broiler farm between January and July 2016. Sixty-six samples of the paper, which were stained with meconium droppings of the chicks, were collected and examined for isolation of cephalosporin-resistant Enterobacteriaceae. Cefotaxime (CTX)-resistant Klebsiella pneumoniae (1 isolate) and Enterobacter cloacae (4 isolates) were isolated from 5 (7.58%) of the 66 samples. Conjugation experiments revealed that the blaCTX-M-25 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The bla CTX-M-8 group was found in E. coli isolated from chicken meats in Brazil [36], humans in the United States [30] and gulls in Spain [52]. The bla CTX-M-25 group was reported from clinical samples in Israel [56] and broiler chickens in Japan [61]. In this study, we found the bla CTX-M-1 group in three ESBL-producing E. coli isolated from rodent feces.…”
Section: Discussionsupporting
confidence: 49%
“…The bla CTX-M-8 group was found in E. coli isolated from chicken meats in Brazil [36], humans in the United States [30] and gulls in Spain [52]. The bla CTX-M-25 group was reported from clinical samples in Israel [56] and broiler chickens in Japan [61]. In this study, we found the bla CTX-M-1 group in three ESBL-producing E. coli isolated from rodent feces.…”
Section: Discussionsupporting
confidence: 49%
“…Resistance against antimicrobials leads to limited therapeutic options, resulting in increasing difficulties of treatments. In contrast to ESBL- producing E. coli which have become very common in veterinary medicine, especially in livestock, companion animals and wildlife, ESBL-producing K. pneumoniae were detected rarely in healthy broiler (Hiroi et al, 2012 ; Yossapol et al, 2017 ; Mahanti et al, 2018 ), diseased horses (Vo et al, 2007 ) dairy cows (Locatelli et al, 2010 ) and in companion animals (Ewers et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In our previous study, CTX-M-25-producing Enterobacteriaceae were isolated from day-old chicks on the date of arrival at the farm. 5 In another previous study, CTX-M-3producing Enterobacteriaceae were isolated from the same broilers at different ages within a flock, suggesting that AMR bacteria persist in birds throughout their entire life. 6 Based on these results, the transfer of CTX-M-type extended-spectrum β-lactamase (ESBL) plasmids among Enterobacteriaceae may be associated with the persistence of CTX-M-producing bacteria in broiler farms.…”
Section: Introductionmentioning
confidence: 81%